Pengembangan media pembelajaran berbasis metode komputasi pada materi larutan elektrolit dan non elektrolit - Harahap, Annisa Sabbilla; Hia, Erlin Karya Kasih; Nugraha, Asep Wahyu (Educenter : Jurnal Ilmiah Pendidikan, 2022)
The purpose of this study was to determine the results of the analysis of needs and feasibility of learning media based on computational methods on electrolyte and non-electrolyte solution materials. This research was conducted in the odd semester of the 2021/2022 academic year at the Computational Chemistry Laboratory, Chemistry Department, Faculty of Mathematics and Natural Sciences, State University of Medan. The population in this study was a simple molecular structure. The sample used in this study were high school students. The instruments used were validation sheets and questionnaires. The types of data used in this study were qualitative data and quantitative data. The analysis includes needs analysis and analysis of media validation. The results obtained in this study indicate that learning media based on 3D visualization and molecular animation using NWChem Software on the sub-topic of electrolyte and non-electrolyte solutions in high school based on BNSP from the assessment of material experts obtained an average percentage of the very feasible category and the feasibility and suitability of the media with the feasible category. It can be concluded that the learning media based on the 3D visualization and molecular animation computational method that has been developed is very feasible to use.